Analisis Tindak Tutur Ilokusi pada Playlist “Sejarah” dalam Channel Youtube Quipper Indonesia - Nayla Syarifa; Intana Aura Izza; Izatul Atiya Pasah; Indah Zahri Rahmawati; Listiana Pramudita; Nayla Putri Dewi Lestari; Asep Purwo Yudi Utomo; Vera Krisnawati (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
The purpose of this study is to determine and identify the types of illocutionary speech acts in the history playlist on Quipper Indonesia The purpose of this study is to determine and identify the types of illocutionary speech acts in the history playlist on the Quipper Indonesia YouTube channel, which contains seven videos. This study uses a methodological approach and a theoretical approach. The methodological approach is used to describe the provisions of the survey. At the same time, the theoretical approach is used as a basis for reviewing the study. At the same time, the theoretical approach used is pragmatic. The method used in this study is a qualitative descriptive method. The data collection process is completed in three stages, namely (1) data collection, (2) data analysis, and (3) data presentation. Data was collected using the free listening technique, folding conversation, and the kata technique. Then the data analysis technique was then used the match and distribution method. Finally, the data is presented using formal and informal processes. In this study, 105 data were found with details of 73 assertive utterances, 16 directive utterances, 3 declarative utterances, 6 commissive utterances, and 8 expressive utterances. This study also aims to improve understanding of illocutionary speech acts and identify various types of illocutionary speech acts that appear in learning videos on the Quipper Indonesia Youtube channel on the “History” Playlists.